Simulation - Ross, Sheldon M. (London, United Kingdom : Academic Press, an imprint of Elsevier, 2023)
Simulation, Sixth Edition continues to introduce aspiring and practicing actuaries, engineers, computer scientists and others to the practical aspects of constructing computerized simulation studies to analyze and interpret real phenomena. Readers will learn to apply the results of these analyses to problems in a wide variety of fields to obtain effective, accurate solutions and make predictions. By explaining how a computer can be used to generate random numbers and how to use these random numbers to generate the behavior of a stochastic model over time, this book presents the statistics needed to analyze simulated data and validate simulation models. --
1 : Introduction -- 2 : Elements of probability -- 3 : Random numbers -- 4 : Generating discrete random variables -- 5 : Generating continuous random variables -- 6 : The multivariate normal distribution and copulas -- 7 : The discrete event simulation approach -- 8 : Statistical analysis of simulated data -- 9 : Variance reduction techniques -- 10 : Additional variance reduction techniques -- 11 : Statistical validation techniques -- 12 : Markov chain Monte Carlo methods
Previous edition: 2013.
Includes bibliographical references and index.
Keywords: Random variables; Probabilities; Computer simulation; Computer simulation; Probabilities; Random variables